Humoral Immune Response in Acute Hepatitis C Virus Infection - Netski, Dale M.; Mosbruger, Tim; Depla, Erik; Maertens, Geert; Ray, Stuart C.; Hamilton, Robert G.; Roundtree, Stacy; Thomas, David L.; McKeating, Jane; Cox, Andrea (Clinical infectious diseases, 2005)
Background. There is little information on the timing, magnitude, specificity, and clinical relevance of the antibody response to acute hepatitis C virus (HCV) infection. We investigated the specificity, titer, and neutralizing potential of antibody responses to acute infection by examining 12 injection drug users before, during, and after infection. Methods. Seroconversion was defined as incident detection of HCV-specific antibodies by using a commercially available enzyme-linked immuosorbent assay (ELISA). HCV protein—specific antibody responses were measured using recombinant antigens in an ELISA. For neutralization assays, plasma was incubated with human immunodeficiency virus (HIV)—HCV H77 or control HIV—murine leukemia virus (MLV) pseudotype virus and then allowed to infect Hep3B hepatoma cells. Results. The mean time to HCV seroconversion was 6 weeks after the onset of viremia. Antibody responses to nonstructural proteins were detected before responses to the structural proteins, and antibodies to both were primarily restricted to the immunoglobulin G1 (IgG1) subclass. The maximum median end point titers for antibody responses to structural and nonstructural proteins were 1 : 600 and 1 : 6400, respectively. Antibodies that neutralized a retroviral pseudotype bearing HCV 1a envelope glycoproteins were detected at seroconversion in only 1 subject and at 6–8 months after seroconversion in 3 subjects. The delayed appearance of neutralizing antibodies was consistent with the late development of antibodies specific for the viral envelope glycoproteins, which are believed to mediate virus neutralization. Conclusion. The humoral immune response to acute HCV infection is of relatively low titer, is restricted primarily to the IgG1 subclass, and is delayed. A better understanding of why production of neutralizing antibody is delayed may improve efforts to prevent HCV infection.